2017
DOI: 10.1002/ldr.2701
|View full text |Cite
|
Sign up to set email alerts
|

Soil Reserves of Potassium: Release and Availability to Lolium perenne in Relation to Clay Minerals in Six Cropland Soils from Eastern China

Abstract: An 8‐month greenhouse experiment with ryegrass (Lolium perenne L.) examined the relationship between the dynamics of potassium (K) reserves in soil and changes in clay minerals, using X‐ray diffraction. The capacity of soil to release K was consistent with its ability to supply it and was the highest in the soil samples collected from Laiyang (H1T2a), Harbin (H1T1) and Beibei (H2T4), followed by the sample from Jiangyan (H1T2b), and the lowest in the samples from Gao'an (H2T3a) and Wangcheng (H2T3b). Removal o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
9
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 26 publications
(13 citation statements)
references
References 70 publications
4
9
0
Order By: Relevance
“…Recently, Moterle et al (2016) using X-ray decomposition methods found that the removal of K from the illite interlayers transformed the clay mineral into vermiculite, a fact that had a positive effect on soil exchange capacity. The above was also confirmed by Li et al (2017) using the same X-ray curve decomposition techniques.…”
Section: Discussionsupporting
confidence: 62%
See 2 more Smart Citations
“…Recently, Moterle et al (2016) using X-ray decomposition methods found that the removal of K from the illite interlayers transformed the clay mineral into vermiculite, a fact that had a positive effect on soil exchange capacity. The above was also confirmed by Li et al (2017) using the same X-ray curve decomposition techniques.…”
Section: Discussionsupporting
confidence: 62%
“…Potassium (K) is an essential macronutrient for higher plants and although has been studied extensively, the complexity of K release and fixation in soils is the main reason that the mechanisms that control K availability to plants remain as yet unclarified. K dynamics is considered as a dynamic chemical equilibrium that connects the three distinct forms of K in soils (soil solution K, exchangeable, and non-exchangeable K) that are assumed as plant available (Huang 2005), while the presence of 2:1 clay minerals influences the ability of the soil to release non-exchangeable K and therefore determines K availability (Li et al 2017).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, in this study, except for unfertilized pots, diagnostic leaf analysis did not reveal insufficient levels of any nutrient (data not shown) that could explain the decrease in dry matter production. Despite plant uptake of K from fractions that are less soluble than exchangeable K, uptake and removal of soil K over successive crop cycles can eventually lead to a decrease in K and dry matter production [43][44][45]. The use of ruzigrass to deplete soil exchangeable K was very effective (Figure 2A), as observed in previous studies [34].…”
Section: Discussionsupporting
confidence: 62%
“…[ 1 ] The exhaustion of available nutrients in the soil is among the main factors that can aggravate the degradation process, thus, increasing nutrient availability to plants in degraded areas is a key factor for restoration. [ 2 ] Phosphorus (P) and potassium (K) are two of the most limiting nutrients for plant growth and their concentrations in degraded areas are usually below plant demand. [ 3 ] Degraded soils are generally acidic, with low nutrient availability, low cation exchange capacity (CEC), and high anion adsorption capacity; [ 4 ] in other words, these areas have low agricultural aptitude and even with periodic fertilization, significant losses of P and K can occur.…”
Section: Introductionmentioning
confidence: 99%